2015
DOI: 10.1208/s12249-014-0269-6
|View full text |Cite
|
Sign up to set email alerts
|

Stability-enhanced Hot-melt Extruded Amorphous Solid Dispersions via Combinations of Soluplus® and HPMCAS-HF

Abstract: The aim of this study was to evaluate a novel combination of Soluplus® and hypromellose acetate succinate (HPMCAS-HF) polymers for solubility enhancement as well as enhanced physicochemical stability of the produced amorphous solid dispersions. This was accomplished by converting the poorly water-soluble crystalline form of carbamazepine into a more soluble amorphous form within the polymeric blends. Carbamazepine (CBZ), a Biopharmaceutics Classification System class II active pharmaceutical ingredient (API) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 24 publications
2
35
0
1
Order By: Relevance
“…Alshahrani et al (69) utilized HME technology in the preparation of carbamazepine (CBZ) solid dispersions using a novel combination of Soluplus® and the HF grade of the polymer hydroxypropyl methylcellulose acetate succinate (HPMCAS-HF, also called hypromellose acetate succinate in pharmaceutical applications) to enhance the solubility and physicochemical stability of the amorphous solid dispersion product. Soluplus® is polyethylene-glycol-polyvinyl caprolactam-polyvinyl acetate-grafted copolymer that was specifically designed and developed for HME by BASF SE.…”
Section: Pharmaceutical Applications Of Hme Solid Dispersions For Solmentioning
confidence: 99%
See 1 more Smart Citation
“…Alshahrani et al (69) utilized HME technology in the preparation of carbamazepine (CBZ) solid dispersions using a novel combination of Soluplus® and the HF grade of the polymer hydroxypropyl methylcellulose acetate succinate (HPMCAS-HF, also called hypromellose acetate succinate in pharmaceutical applications) to enhance the solubility and physicochemical stability of the amorphous solid dispersion product. Soluplus® is polyethylene-glycol-polyvinyl caprolactam-polyvinyl acetate-grafted copolymer that was specifically designed and developed for HME by BASF SE.…”
Section: Pharmaceutical Applications Of Hme Solid Dispersions For Solmentioning
confidence: 99%
“…The FTIR data demonstrated that the intensity of the hydrogen bonding was increased by the addition of HPMCAS-HF, which worked synergistically with the Soluplus® to enhance the solubility and stability of the formulation. These researchers also studied the effect of the polymer ratio on the extrudability and dissolution profile and found that the release of CBZ was enhanced with an increase in the percentage of Soluplus® (69).…”
Section: Pharmaceutical Applications Of Hme Solid Dispersions For Solmentioning
confidence: 99%
“…Still, Soluplus® has been shown to enhance solubility to a greater extent for certain APIs relative to other hydrophilic polymers (97). The utility of Soluplus® as a matrix polymer and solubility enhancer in melt-extruded ASDs has been demonstrated for multiple poorly water-soluble drugs, including carbamazepine (95,96,98), fenofibrate (99), simvastatin (100), dronedarone hydrochloride (101), and valsartan (102).…”
Section: Designer Polymers For Extrusion Processingmentioning
confidence: 99%
“…14) Considering this background, Soluplus ® has been applied to solid dispersion formulations prepared by freeze-drying, spraydrying, and melt-extrusion techniques to enhance the solubility and bioavailability of poorly water-soluble compounds. [15][16][17] However, the solubilizing mechanism of Soluplus ® ascribed to micellization has yet to be elucidated. The self-organization of surfactants and amphiphilic polymers into micelles has been widely researched using many analytical methods, including the measurement of surface tension, Fourier transform infrared spectroscopy, relaxation studies using 1 H nuclear magnetic resonance, fluorescence spectroscopy, and isothermal titration calorimetry (ITC).…”
mentioning
confidence: 99%